Horticultural use of organic waste treatment plant of Villanueva, Casanare, Colombia (Revista Sistemas de Producción Agroecológicos, 2014)
This study aimed to identify usage from leachate treatment plant solid waste in the municipality of Villanueva Casanare, and get to know the potential it offers for use as fertilizer on crops. On the ground of comprehensive solid waste management in the municipality of Villanueva Casanare, organic material, ground and is then used in vermiculture as food formed a earthworm-compound, where later the leachate was extracted to perform a study on the potential use as fertilizer on cucumber crops (Cucumis sativus) , in order to promote the development of agriculture in the region, making the cost comparison of the different treatments used to establish the comparative advantage of them, relating the presence of insect pests, beneficial organisms and diseases. The treatments were: T0: Chemical fertilizer, T1: 100% earthworm-compound, T2: 100% leachate, and T3: 50% leachate and 50% leachate earthworm-compound. Cucumber crop responded well to organic fertilization, unable to overcome the chemical control in production. Better performance in the chemical treatment, a total of 3837 kg/ha, with a yield of 14.03% was obtained while the organic treatments, the best results were achieved in 50% leachate treatment and 50% vermicompost, yield of 3360.26 kg/ha, which is the more profitable (48.1%) treatment.
Keywords: organic fertilizer; leachate; horticulture; vermiculture